Genre et discours métaphoriques sur la traduction - Lori Chamberlain (Glad!)
In 1988, in « Gender and the Metaphorics of Translation », Chamberlain revisits the figure of translation through several centuries of metaphors in translation studies. Based on the study of texts and anthologies from 1958 to 1985, particularly major texts such as those by Serge Steiner and Serge Gavronsky (and by those who inspired them from 1684 like Roscommon, Franklin or Cowper), she draws on Jacques Derrida, Terry Eagleton, Joseph Graham, Carole Maier, Suzanne Jill Levine or Susan Gubar, by deepening their approach, to analyze both the subordinate status given to translation by great translation scholars in the face of writing, but also the sexualized and submissive relationship it is supposed to have with the original text. This analysis, written during the emergence of feminist translation studies across the Atlantic, challenges a masculine and sexist conception of translation and creativity written about in terms of domination, power, gender and violence. By removing the seductive mask of stylistic beauty from the texts by translation scholars such as Steiner or Gavronsky, she reminds us that any sexist and hierarchical vision of creativity (creation vs. re-creation) is not simply problematic from a symbolic point of view, but that it underlies a struggle for authorship of texts that has material repercussions in terms of academic and salary recognition, or copyrights. With the agenda of freeing translation studies, the female translator and all creative acts from the yoke of limiting prejudices such as the binarity and hierarchy of the sexes (men/women) of works (original text/derived text) and of creation (calque/belles infidèles), Lori Chamberlain also questions an ultimately primitive, vision of anthropological relationships that are supposed to be based, as colonization was, on lust, greed, lust and violence, and that have long been conveyed in the metaphors of translation built around "the exchange of words, women and goods" (Lévi-Strauss). She goes further by proposing a real program for feminist translation studies that enable a dialogue with disciplines other than literature or philosophy: such as history or sociology.